Reproductive Dynamics of the Seabob Shrimp Xiphopenaeus kroyeri in Trawl Fisheries in Southeastern Brazil - Santos, Amanda Soares dos; Craveiro, Cecília Fernanda Farias; Castro-Neto, Hildemário; Bernabé, Caroline Vettorazzi; Mattos, Douglas da Cruz; Cardoso, Leonardo Demier; Oliveira, Adriano Teixeira de; Aride, Paulo Henrique Rocha; Lavander, Henrique David; Silva, Maria Aparecida da (Biology (Basel, Switzerland), 2025)
Seabob shrimp Xiphopenaeus kroyeri is under heavy capture-pressure in the western Atlantic, requiring periods of fishing suspension to protect the propagation of the species in the wild. This work aims to describe the stages of gonadal development and the ovaries of X. kroyeri in trawling in the southeastern Atlantic Ocean of Brazil associated with climatic characteristics of temperature and precipitation. In total, 3658 specimens were captured in monthly collections from March 2019 to February 2020. The female gonads were classified macroscopically and microscopically according to the maturation stage and correlated with precipitation and temperature data. Five stages of maturation were observed: immature, initial maturation, advanced maturation, mature, and spawned. The highest percentage of mature females was found in May and July, and the average size of the female cephalothorax at the first gonadal maturation was 1.7 cm. The recruitment period was observed in April, with more juveniles. Precipitation showed a negative correlation with the number of mature females. April, May, and July are essential for the life cycle of the X. kroyeri population on the coast of Espírito Santo, Brazil. The results suggest that the current closed season for the species should be reconsidered.